Bacteria From the Southern Gulf of Mexico: Baseline, Diversity, Hydrocarbon-Degrading Potential and Future Applications - Rodríguez-Salazar, Julieta; Loza, Antonio; Ornelas-Ocampo, Katya; Gutierrez-Rios, Rosa Maria; Pardo-López, Liliana (Frontiers in Marine Science, 2021)
The Gulf of Mexico Research Consortium (Consorcio de Investigación del Golfo de México (CIGoM), 2020) was founded in 2015 as a consortium of scientific research and consulting services, specializing in multidisciplinary projects related to the potential environmental impacts of natural and human-induced oil spills in marine ecosystems, to understand and act in the case of possible large-scale oil spills in the Gulf of Mexico. CIGoM comprises more than 300 specialized researchers trained at the most recognized Mexican institutions. Among the main interests of CIGoM are developing the first baseline of the bacterial community inhabiting the southern Gulf of Mexico, investigating the natural degradation of hydrocarbons by bacterial communities and microbial consortia and identifying and characterizing industrially relevant enzymes. In this review, using third-generation sequencing methodologies coupled to function screening methodologies, we report the bacterial profile found in samples of water and sediments in Mexican regions that include the Perdido Fold Belt (northwest of Mexico), Campeche Knolls (in the southeast) and Southwest region of the Gulf of Mexico. We also highlight some examples of novel lipases and dioxygenases with high biotechnological potential and some culturable hydrocarbon-degrading strains used in diverse bioremediation processes.